Investigation of the effects of fabrication tolerances in microwave thick-film circuits - Mohd Shah, Shaharil (2004)
This project dealt with the design and fabrication of bandpass filter centered at 16 GHz using modem thick-film technology. The rapid development of the commercial microwave circuits requires a low cost, cheaper technology to replace the old, more expensive thin-film technology. Therefore, thick-film technology is the best alternative. The effects of fabrication tolerances in the physical dimensions of various parameters were being investigated as well. The analysis of the result can then be applied to determine the trade off between perfOlmance and tolerances. It is therefore extremely important to control the vmiations of parameters in microstlip with fablication tolerances to achieve the desired perfonnance.